What languages are chosen in Malaysian family domain? The case of Malay, Chinese and Indian undergraduates. - Mostafizar Rahman, A. R. M.; Chan, Swee Heng; Abdullah, Ain Nadzimah (2008)
People in multilingual societies choose and use language depending on the contexts, activities, role relationships, gender and other ethno-linguistic background. Malaysia being a multilingual and multicultural country, what languages are chosen in the family domain constitutes the focus and objectives of this paper. The patterns of language choice among the university undergraduates of Malay, Chinese and Indian ethnic groups in the family domain were obtained through a questionnaire survey administered in November and December, 2006 at the University Putra Malaysia and the data were analyzed using SPSS. It is found that ethnic languages were found to be preferred in the family domain. Bahasa, Melayu and English were also reported to be chosen in this domain which could be attributed to domain allocation of language use and role-relationships among the family members. Ethnicity and proficiency were also found to play important role in the choice of language.